Oral health conditions of adolescents in socially vulnerable situations: literature review (Research, Society and Development, 2021)
Introduction: The World Health Organization (WHO) considers adolescents aged 15 to 19 years. It is at this stage that marked changes take place and remain throughout life. There is great concern with the body and appearance, including in this context oral health, which is also part of individual well-being. Objective: This study aims to present factors that can influence the oral health of adolescents between 15 and 19 years old, in a condition of social vulnerability, through a literature review and the results of the Oral Health Surveys (SB Brasil) carried out in 2003 and 2010. Methodology: This is a literature review with a descriptive approach. Results and Discussion: However, the social situation of vulnerability associated with precarious living conditions are factors that leave apparent registers in the mouth, in the smile of these teenagers, increasing the rates of tooth decay and tooth loss in teenagers with low income, low educational level, lack access to oral health services, associated with a cariogenic diet. Conclusion: As a consequence, the self-esteem of adolescents who suffer early tooth loss is impaired by malocclusion, causing a lack of confidence, compromised activities, lack of motivation and communication difficulties.